2015
DOI: 10.1097/mao.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of Psychophysical Parameters Between Perimodiolar and Lateral-type Electrode Arrays in Patients With Bilateral Cochlear Implants

Abstract: Although the level of electrical energy required for auditory stimulation seems to be lower for the perimodiolar electrode array than for the laterally placed array, the DR was wider and the amount of battery consumption was similar. The electrode array should be chosen by considering various patient factors, such as residual hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Several studies have demonstrated lower stimulation thresholds for permodiolar arrays than for straight arrays, either when measured psychophysically or when assessed by objective measures [Cohen et al, 2001;Gordin et al, 2009;Runge-Samuelson et al, 2009;Jeong et al, 2015;Müller et al, 2015;Telmesani and Said, 2015]. Other studies have reported a reduced spread of excitation using forward masking ECAP paradigms [Hughes and Abbas, 2006;Basta et al, 2010;Hughes and Stille, 2010] with improved spectral discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated lower stimulation thresholds for permodiolar arrays than for straight arrays, either when measured psychophysically or when assessed by objective measures [Cohen et al, 2001;Gordin et al, 2009;Runge-Samuelson et al, 2009;Jeong et al, 2015;Müller et al, 2015;Telmesani and Said, 2015]. Other studies have reported a reduced spread of excitation using forward masking ECAP paradigms [Hughes and Abbas, 2006;Basta et al, 2010;Hughes and Stille, 2010] with improved spectral discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of current literature evaluating effects of charge on array type reports that perimodiolar placements result in reduced charge for equivalent stimulation at threshold and at suprathreshold comfort levels (3, 56) and lower EABR thresholds (78). There are, however, a few published studies that have reported contrasting results.…”
mentioning
confidence: 99%
“…As might be expected, compound action potential thresholds, T levels and C levels were lower in perimodiolar arrays but there was not any significant difference in dynamic range [27]. This study did not follow patients for long enough to comment on timing for stability, but given the lack of difference in dynamic range between array types, it would be unlikely to be an important variable for map stability.…”
Section: Array Typementioning
confidence: 90%